1990
DOI: 10.2172/6945131
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of health effects in Sequoyah Fuels Corporation workers from accidental exposure to uranium hexafluoride

Abstract: Urine bioassay ~easurements for uranium and medical laborato ry resu~ts were studied to determine whether there were any health effects from urcnium intake among a group of 31 workers exposed to uranium hexafluoride (UF6) and hydrolysis products following the accidental rupture of a 14-tun shipping cylinder in early 1986 at the Sequoyah FJels Corporation uranium conversion facility in Gore, Oklahoffid. Physiological indicators studied to detect kidney tissue damage inc "i uded tests for urinary protein, casts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Studies at the Pacific NorthwestLaboratory(PNL) on urine data obtained from Sequoyah Fuels Corporationworkers after the 1986 UF6 rupture accident showed that a maximum likely kidney tissue concentrationof about 2.5 _g U per g of kidney tissue occurred in the highest-exposed workers. No _ong-termkidney tissue damage was observed at these concentrations,but there was some evidence of increasedurinary protein in the highest-exposed workers (Fisher et al 1990). The clinical laboratoryevidence from this study suggestedthat uranium concentrationsin kidneysof these workers may approached,but not exceed, the threshold for toxicity in humans.…”
Section: Nephrotoxic Threshol Dmentioning
confidence: 90%
“…Studies at the Pacific NorthwestLaboratory(PNL) on urine data obtained from Sequoyah Fuels Corporationworkers after the 1986 UF6 rupture accident showed that a maximum likely kidney tissue concentrationof about 2.5 _g U per g of kidney tissue occurred in the highest-exposed workers. No _ong-termkidney tissue damage was observed at these concentrations,but there was some evidence of increasedurinary protein in the highest-exposed workers (Fisher et al 1990). The clinical laboratoryevidence from this study suggestedthat uranium concentrationsin kidneysof these workers may approached,but not exceed, the threshold for toxicity in humans.…”
Section: Nephrotoxic Threshol Dmentioning
confidence: 90%
“…The renal toxicity of uranium varies with the compound form, with toxicity increasing with chemical solubility (Morrow et al 1982). Based on work by Just (1984), Just and Emler (1984), and Fisher, Swint, and Kathren (1990), McGuire (1991) concluded that an acute intake of soluble uranium of 10 mg or less is unlikely to have any detectable (even transient) effects, and that a 40-mg intake (possibly as high as 100 mg) is likely to be below the level of any permanent effects. …”
Section: Chemical Toxicitymentioning
confidence: 99%
“…Albuminuria is also an indicator of kidney damage. Leggett (1989) and Fisher, Swint, and Kathren (1990) have identified a number of other potentially useful tests. The decision to perform such tests is made by HEHF Occupational Medicine.…”
Section: Assessment Of Kidney Burden and Potential Chemical Toxicitymentioning
confidence: 99%
“…Data are available for a number of other cases with acute inhalation intakes estimated to be several tens of mg of uranium, all of whom showed minor transitory renal effects as evidenced by biomarkers in the urine, but all of whom recovered within days after exposure (Boback 1975;Fisher et al 1990;Kathren and Moore 1986). Also, Butterworth (1955) reported a case of voluntary experimental ingestion of 470 mg of uranium as uranyl nitrate by a male subject, with complete recovery from minor renal effects within 24 h.…”
Section: Establishment Of Level For Irreversible or Serious Long Lastmentioning
confidence: 99%
“…Once again based on animal studies, the relatively insoluble compounds such as UO 2 , U 3 O 8 , and UF 4 exhibit a low order of chemical toxicity because they are poorly absorbed via the gut or respiratory tract, while the more soluble compounds of uranium such as Na 2 U 2 O, UO 2 (NO 3 ) 2 , and UO 4 are more quickly absorbed into the blood and therefore exhibit toxic effects in moderate doses (ATSDR 1999;Stannard 1988). UO 2 F 2 and UF 6 constitute a special case because they hydrolyze to yield HF which produces corrosive chemical effects (acid burns) on tissues independent of uranium chemical toxicity or enrichment (Tannenbaum and Silverstone 1951;Kathren and Moore 1986;Fisher et al 1990). …”
Section: Introductionmentioning
confidence: 99%